Web Integrated STEM Learning: Effects on Students’ Academic Achievement, Creativity and Metacognitive Awareness - Ayberk Bostan Sarıoğlan; Özge Şentürk Özkaya (Journal of Science Learning, 2023)
This study examines the effect of teaching with the STEM Cycline of the 'Force and Energy' unit on students' creativity, metacognitive awareness, and academic achievement. The nonequivalent control group design, one of the quasi-experimental models, was used in the study. The study included 54 seventh-grade students studying at a public school in western Turkey, 27 of whom were in the experimental group while 27 were in the control group. The experimental group was taught with the STEM Cycline, whereas the control group took the instruction within the science curriculum framework. The experimental group designed models using Web 2.0 tools related to the given problems and used these models to solve them by printing them from a 3D printer. "Force and Energy Academic Achievement Test", "Scientific Creativity Test" and "Metacognitive Awareness Inventory" were used as data collection tools in the study. SPSS 25.0 package program was used to analyze the data. The results showed that the STEM education in the experimental group increased the academic achievement, creative skills, and metacognitive awareness of the seventh-grade students in the 'Force and Energy' unit. While the students’ academic achievement in the control group increased significantly following the instruction, no difference was observed in their creativity and metacognitive awareness. Suggestions were made according to the results obtained from the study.